2008
DOI: 10.22198/rys.2008.43.a494
|View full text |Cite
|
Sign up to set email alerts
|

Contaminación y control de las quemas agrícolas en Imperial, California, y Mexicali, Baja California

Abstract: La quema de residuos agrícolas en los valles de Mexicali e Imperial, separados por una línea divisoria, constituye una fuente importante de emisión de contaminantes al aire, de compuestos como el metano (ch4), monóxido de carbono (co), bióxido de nitrógeno (no2), hidrocarburos (nmhc) y partículas menores a 10 micras (pm10). Para abordar el problema de los humos agrícolas se debe considerar la cuenca atmosférica común, formada por ambos valles, que comparten un clima extremoso cálido y seco, con menos de 80 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…El Triticum aestivum (trigo) es el cultivo más extendido a nivel mundial, sembrado en 115 países con una producción de 675 x 10 9 kg año -1 (Kim & Dale 2004, FAO 2012. Como resultado se genera como subproducto un estimado de 877 x 10 9 kg de paja residual (Talebnia et al 2010), cuya disposición final es comúnmente la incineración "in situ", con un impacto ambiental negativo, por la emisión de partículas en suspensión (PM10) y gases CO, CO2, NO2, SO2, O3 (Li et al 2008, Quintero-Núñez & Moncada-Aguilar 2008. La paja de trigo está constituida por remanentes estructurales de la pared celular vegetal: celulosa (39%), hemicelulosa (38.7%) lignina (17%) (Xu et al 2006).…”
Section: Introductionunclassified
“…El Triticum aestivum (trigo) es el cultivo más extendido a nivel mundial, sembrado en 115 países con una producción de 675 x 10 9 kg año -1 (Kim & Dale 2004, FAO 2012. Como resultado se genera como subproducto un estimado de 877 x 10 9 kg de paja residual (Talebnia et al 2010), cuya disposición final es comúnmente la incineración "in situ", con un impacto ambiental negativo, por la emisión de partículas en suspensión (PM10) y gases CO, CO2, NO2, SO2, O3 (Li et al 2008, Quintero-Núñez & Moncada-Aguilar 2008. La paja de trigo está constituida por remanentes estructurales de la pared celular vegetal: celulosa (39%), hemicelulosa (38.7%) lignina (17%) (Xu et al 2006).…”
Section: Introductionunclassified
“…Therefore, we recommend further studies to collect biological information for these sites. Considering that this region is subject to multiple threats as habitat modification, pollution, introduction of exotic species, and other processes that are affecting ecosystems ( Valdés-Casillas et al 1998 ; Quintero-Núñez and Moncada-Aguilar 2008 ; Rosete-Vergés et al 2008 ; Andreu-Soler et al 2014 ), we consider crucial that all NPAs are included in future evaluations of the conservation potential in the northern Peninsula, regardless of their type of governance. Other studies have shown that non-government NPAs can have considerable complementarity with government NPAs , and that they contribute to secure the protection of a higher proportion of biodiversity ( Ochoa-Ochoa et al 2009 ; Muench and Martínez-Ramos 2016 ; García-Bañuelos et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to comment that agricultural burning is a traditional activity of Mexican farmers in early spring as it is the cheapest procedure to get rid of products that remain in the field after harvest. [65][66][67]. It is also true that in spring, temperature rises significantly, as Romero and Sarricolea, in 2006, found a linear relationship between atmospheric temperatures and particulate matter, in addition to a strong correlation among soil use and cover on temperature elevation, which can exacerbate health effects of chronic diseases like cardiovascular and respiratory illnesses [68,69].…”
Section: Discussionmentioning
confidence: 99%